ITPR1 variant-induced autosomal dominant hereditary spastic paraplegia in a Chinese family - Li, Rui; Liu, Xuan; Ke, Chenming; Zeng, Fanli; Zeng, Qingyi; Xu, Xiaowei; Fan, Xiaoqin; Zhang, Ying; Hou, Qinghua (Frontiers in Neurology, 2024)
Hereditary spastic paraplegia (HSP) is a rare neurodegenerative disease prominently characterized by slowly progressive lower limb weakness and spasticity. The significant genotypic and phenotypic heterogeneity of this disease makes its accurate diagnosis challenging. In this study, we identified the NM_001168272: c.2714A > G (chr3.hg19: g.4716912A > G, N905S) variant in the ITPR1 gene in a three-generation Chinese family with multiple individuals affected by HSP, which we believed to be associated with HSP pathogenesis. To confirm, we performed whole exome sequencing, copy number variant assays, dynamic mutation analysis of the entire family, and protein structure prediction. The variant identified in this study was in the coupling domain, and this is the first corroborated report assigning ITPR1 variants to HSP. These findings expand the clinical and genetic spectrum of HSP and provide important data for its genetic analysis and diagnosis.